Dampak Kecanduan Gadget Terhadap Emosional Anak Di Kelas 6 Sekolah Dasar - Uttami, Desri; Fitriyeni, Fitriyeni (Cetta: Jurnal Ilmu Pendidikan, 2024)
Many students who are addicted to gadgets tend to spend more time interacting with digital devices than interacting directly with other people. Lack of social interaction has an impact on children's ability to develop communication skills, empathy and social understanding. The aim of this research is to describe how gadget addiction has an emotional impact on children in class VI at SDN 006 Sorek Dua. This research design uses quantitative descriptive research methods. The population in this study was all 46 class VI students. The sample selection technique used a totaling sample, so the sample in this study was 46 students. In this research, the data collection technique uses a questionnaire and the instrument is a questionnaire sheet. The data analysis technique in this research uses percentage data. Based on the research findings, it can be concluded that the impact of gadget addiction on children's emotions in class VI students at SDN 006 Sorek Dua on the variables of gadget addiction and children's emotions is in the medium category.